Understanding of the Laws of the Game 2025/2026 on the Quality of Football Referees in the Semarang City PSSI - Andre Juan Rustu Bumi; Ipang Setiawan (Universitas Negeri Semarang, 2026)
Football is the most popular sport in the world, with more than 250 million active players spread across more than 200 countries according to the IFAB Annual Report. The purpose of this study was to determine the level of understanding of football game rules (Laws Of The Game) among football referees of the Semarang City PSSI Association for the 2025/2026 season. This study used a descriptive quantitative approach. Data collection techniques used questionnaires/surveys. The population in this study consisted of 50 referees, and the sampling technique used total sampling with a sample size of 50 referees. The results of the research data analysis show that the level of understanding of the Laws of the Game among football referees of the Semarang City PSSI Association in 2025/2026 was 28 people (73.38%) in the good category, 17 people (16.11%) in the moderate category, and 5 people (10.51%) in the poor category. This study can be concluded that the understanding of the 2025/2026 Laws of the Game regarding the Quality of PSSI Semarang City Football Referees is in the high category with a total of 28 people (73.38%).